(untitled) (European Journal of Pure and Applied Mathematics, 2025)
The Arag\’on Artacho–Campoy algorithm (AACA) is a new method for finding zeros of sums of monotone operators. In this paper we complete the analysis of their algorithm by defining their operator using Douglas Rachford operator and then study the effects of the order of the two possible Arag\’on Artacho–Campoy operators.